2011
DOI: 10.1021/es200030z
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of Higher Brominated PBDE Congeners in an Urban Terrestrial Food Web in North China Based on Field Observation of Prey Deliveries

Abstract: As an important group of brominated flame retardants, polybrominated diphenyl ethers (PBDEs) persist in the wildlife food webs. However, the biomagnification of PBDEs has not been adequately studied in the terrestrial food webs. In this study, a terrestrial food web composed of common kestrels, sparrows, rats, grasshoppers, and dragonflies in the urban environment from northern China was obtained. A field prey delivery study, reinforced by δ 13 C and δ 15 N analyses, indicates that sparrows are the primary pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 35 publications
7
31
0
Order By: Relevance
“…For instance, aquatic birds were usually BDE-47 accumulated, whereas the birds feeding entirely or partially on terrestrial-based food items had elevated abundance of BDE-153 or higher brominated congeners (Chen and Hale, 2010). Our previous study (Yu et al, 2011) also suggested the particular concern over the bioaccumulation and biomagnification of BDE-209 and its degradation products because of their possibly high ecological risks in terrestrial ecosystems. A study conducted in Belgium also showed indisputable biomagnification of PBDEs in two avian food chains (great titÀsparrowhawk and rodentÀbuzzard feeding relationships), whereas no biomagnification was found in the rodent-fox food chain (Voorspoels et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…For instance, aquatic birds were usually BDE-47 accumulated, whereas the birds feeding entirely or partially on terrestrial-based food items had elevated abundance of BDE-153 or higher brominated congeners (Chen and Hale, 2010). Our previous study (Yu et al, 2011) also suggested the particular concern over the bioaccumulation and biomagnification of BDE-209 and its degradation products because of their possibly high ecological risks in terrestrial ecosystems. A study conducted in Belgium also showed indisputable biomagnification of PBDEs in two avian food chains (great titÀsparrowhawk and rodentÀbuzzard feeding relationships), whereas no biomagnification was found in the rodent-fox food chain (Voorspoels et al, 2007).…”
Section: Introductionmentioning
confidence: 75%
“…Then, the extract was further cleaned up using SPE column chromatography, which has been proven to be an effective method for purifying PBDEs in small samples of biota (He et al, 2010;Yu et al, 2011). In consideration of the large sample volumes used in the present study, a separation step using a complex silica gel column was added between the GPC treatment and SPE column chromatography steps.…”
Section: The Selection Of a Final Methods For Purifying Pbdesmentioning
confidence: 99%
“…One tenth of the extracts of fish carcasses was used to quantify the PBDE congeners using a method described in detail previously (Zeng et al, 2012;Yu et al, 2011). The remaining extracts were used to determine purities and to perform CSIA using the method developed in the present study.…”
Section: Pbde Quantificationmentioning
confidence: 99%
“…Procedures for sample pretreatment have been given in details in our previous study (Yu et al, 2011) with modest modifications. Approximately 1 g muscle tissue was homogenized after lyophilization and Soxhlet extracted with acetone/hexane (1:1, v/v).…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…Flash EA 112 series elemental analyzer coupled with a Finnigan MAT ConFlo III isotope ratio mass spectrometer using freeze-dried subsamples. Specific analytical approach and the assessment of isotopic ratios were previously given elsewhere (Yu et al, 2011).…”
Section: Sample Preparation and Analysismentioning
confidence: 99%